ANALISIS KEAKTIFAN BELAJAR SISWA PADA PEMBELAJARAN PPKN MELALUI PENERAPAN METODE KERJA KELOMPOK DI KELAS IV SD NEGERI 50 KOTA TERNATE - Novita M Taher; Kodrat Hi Karim; Selvi Wulandari (Universitas Khairun, 2022)
These study aims are (1) to determine student learning activities by applying group work methods in class IV SD Negeri 50 Ternate City (2) to find out what student learning activities are through the application of group work methods to class IV SD Negeri 50 Ternate City. The method used in this research is the descriptive qualitative method. Data collection techniques used in this research are, observation, interview, and documentation. This study indicates students' activeness in learning PPKN by applying the group work method in class IV SD Negeri 50 Ternate City. That is, some factors that cause students to be active in PPKN learning are before learning, the teacher should give directions first regarding the material to be discussed later, and if the material is related to the rights and obligations of the teacher, always provide examples that fit / easy so that students quickly understand the material. The factors from the family environment are (students/parents) who have limited cellphones if students get assignments related to the national anthem, students must ride or borrow friends' cellphones, students who do not have internet/data packages, some parents who are busy working (traders) so that they cannot help students in completing their homework (PR). The other factors that cause student activity in PPKN lessons are (that some students already understand Indonesian history, some already understand and have memorized the points of Pancasila, memorize national songs, already understand the rights and obligations).